(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
The aim was to assess the comparative bioavailability of two formulations (200 mg tablet) of sodium valproate in healthy subjects. This open label randomized, two periods, two treatments, two sequence, 2-way crossover design study was conducted in 18 healthy Indian adult subjects. Subjects received sodium valproate 200 mg of either test or reference formulation with a washout period of 7 days. After study drug administration, serial blood samples were collected over a period of 60 hours. Plasma concentrations of Valproic acid were measured by pre-validated LC-MS-MS method. Pharmacokinetic (PK) parameters Cmax, Tmax, t1/2, AUC0-t, AUC 0-∞, and kel were determined for the 2 sodium valproate formulations. Cmax, AUC0-t, and AUC0-∞ were used to test for bioequivalence after log-transformation of plasma data. The formulations were to be considered bioequivalent if the log-transformed ratios of Cmax, AUC0-t, and AUC0-∞ were within the predetermined bioequivalence range of 80% to 125%. A total of 18 healthy subjects were enrolled. No significant differences were found based on analysis of variance, with mean values and 90% confidence intervals of test/reference ratios for these parameters as follows: Cmax, 15.64 versus 15.20μg/ml (90.79 to 115.45); AUC0-t, 72.71 versus 66.95μg.h/ml (96.03 to 124.87); and AUC0-∞, 105.65 versus 98.11μg.h/ml (94.61 to 124.75). In these healthy Indian subjects, results from the PK analysis suggested that the test and reference formulations of sodium valproate 200 mg tablets were bioequivalent. Both the formulations were well tolerated.